Role of early enteral feeding in mild and moderate acute pancreatitis - Roy, Aswin George; T. V., Haridas (International Surgery Journal, 2021)
Background: Timing of enteral feeding in acute pancreatitis was always a matter of controversy. Increasing evidence suggests that early enteral feeding reduces systemic and local complications of pancreatitis and thereby hospital stay. Hence the study has been undertaken to determine the feasibility, advantages and disadvantages of early enteral feeding in mild and moderate acute pancreatitis. Methods: Patients admitted with symptoms and signs suggestive of mild and moderate acute pancreatitis who were started on early enteral feeding (within 48 hours of admission) were included in study. Blood investigation results are used to classify patients accordingly to mild and moderate acute pancreatitis based on Ransons’s score. Patients were followed up and categorized based on development of complications, length of hospital stay. Results: Majority of the patients who were started on early enteral feeding showed significant decrease in complications and hospital stay. Study also suggested that age is a significant risk in development of complications. Gender is not significant in the development of complications. Conclusions: There is significant decrease in rate of systemic complication, local infective and non-infective complications, length of hospital stay among acute pancreatitis patients who were started on early enteral feeding (within 48 hours).